Researching Cyberattacks Methods in Industrial Internet of Things - Євсєєв, В. В.; Демська, Н. П. (My University, 2021)
This work is devoted to the study of modern methods of protecting the access to corporate information in modern Smart Manufacturing built on the basis of IIoT. The authors conduct a comparative analysis of vulnerabilities in IIoT networks, consider the security issues of cyber-physical production systems in Industry 4.0.
Keywords: Industry 4.0; Smart Manufacturing; cyberattacks; cybersecurity